عمل المرأة العراقية بين التحديات الأمنية وإمكانات الواقع الاجتماعي - محمد, سهام كامل; فضل الله, جان سيريل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر المساهمة الاقتصادية للمرأة ذات أهمية كبيرة كونها تمثل نصف الموارد البشرية والتي تعتبر عاملاً إنتاجياً مهماً لتحقيق التنمية الاقتصادية في القطاعات الاقتصادية المختلفة. وبما أن زيادة مساهمة المرأة في النشاطات الاقتصادية سيؤدي إلى رفع معدلات النمو الاقتصادي فإنه يساهم بالتالي في زيادة فرص العمل المتاحة في المجتمع. وعلى الرغم من ضخامة حجم الإنفاق على تعليم المرأة ولكن تبقى مساهمتها الاقتصادية وبالذات في سوق العمل محدودة, حيث إن مشاركة المرأة في سوق العمل تتركز وبنسبة عالية في قطاع التعليم بينما تنخفض هذه المشاركة في القطاع الصحي وربما تنعدم كلياً في معظم القطاعات الاقتصادية الأخرى. وهذا ما يؤكد ضعف مساهمة المرأة العراقية في الاستثمار في الأنشطة الاقتصادية. إن عدم تمكين المرأة في المشاركة الفاعلة في النشاط الاقتصادي سواء في سوق العمل أو في الأنشطة التجارية والاقتصادية المختلفة يعني تعطيل نسبة كبيرة من الموارد الاقتصادية المتاحة وعدم تمكن المرأة القدرة في التحكم في مواردها الاقتصادية والوصول إلى درجة الاستقلالية والاعتماد على الذات والمشاركة الفاعلة في النشاط الاقتصادي، تبين من خلال البحث ارتفاع نسبة الأمية بين النساء وازدياد معدل وفيات الأمهات خلال مدة البحث، إضافة إلى التحديات الأمنية والسياسية والاجتماعية والمعاناة من الفقر وضعف الموارد المالية التي تمثل العائق الأول في وجه تمكين المرأة. The economic contribution of women is of great importance as it represents half of the human resources and productivity, which is an important factor for economic development in various economic sectors. Since the increased contribution of women in economic activities will lead to higher rates of economic growth, it ,thus increases employment opportunities available in the community. In spite of the huge expenditure on women's education, programs formatted and prepared for economic contribution, and development plans on the importance of the positive roles of women, their economic contribution remains limited particularly in the labor market, as the participation of women in the labor market is restricted to the education sector. Also, women's participation in the health sector is low and it is perhaps entirely lacking in most of other economic sectors. This confirms the weak contribution of Iraqi women to invest in economic activities. The lack of women's participation in different economic activities, whether in the labor market or in commercial activities and different economic resources, means to disable a large percentage of available economic resources. It also indicates that women lack the ability to control their economic resources and achieve independence and self-reliance to actively take part in economic activities. Accordingly, we need to review their contribution and to expose the economic reality of such issue highlighting the most important challenges that hinder their participation. We will propose appropriate solutions to prevent such waste of our community resources and enable women to participate actively and achieve economic independence so they can care for themselves and their families in case of losing the house' breadwinner. This disruption and this failure in women's roles will reflect negatively on the size of gross domestic product. The research has found high rates of illiteracy and mortality among women during the period of study. In addition to security, political and social challenges, women also suffer from poverty and limited financial resources, which represent the first obstacle in the face of women's empowerment.